Preventing rheumatic fever: M-protein based vaccine - Rajendra Tandon (Indian Heart Journal, 2014)
Group A beta hemolytic streptococcus (GAS), the organism which initiates rheumatic fever (RF) continues to be sensitive to penicillin. However, penicillin cannot prevent RF if the preceding sore throat is asymptomatic in more than 70 percent children. Prevention of rheumatic fever (RF) may be possible only with the use of a vaccine. Efforts to design a vaccine based on emm gene identification of GAS, M-protein going on for more than 40 years, is unlikely to succeed. M-protein is strain specific. Infection with one strain does not provide immunity from infection with another strain. Based on the emm gene identification, of 250 or more identified strains of GAS, the distribution is heterogenous and keeps changing. The M-protein gene sequence of the organism tends to mutate. A vaccine prepared from available strains may not be effective against a strain following mutation. Lethal toxic shock syndrome due to GAS infection has been described with organisms without identifiable or functional M-protein. M-protein has been excluded as the antigen responsible for acute glomerulonephritis (GN). Therefore M-protein plays no role in one suppurative (toxic shock syndrome) and one non-suppurative (acute GN) manifestation due to GAS infection. Lastly there is no direct evidence to indicate that M-protein is involved in inducing RF. The role of M-protein and the GAS component resulting in the suppurative manifestations of GAS infections like pyoderma, septic arthritis or necrotizing fasciitis etc is unknown. For a vaccine to be effective, an epitope of the streptococcus which is stable and uniformly present in all strains, needs to be identified and tested for its safety and efficacy. The vaccine if and when available is expected to prevent GAS infection. Preventing GAS infection will prevent all the suppurative as well as non-suppurative manifestations including RF.